IMPLEMENTASI PROGRAM BADAN USAHA MILIK DESA (BUMDES) BERBASIS SYARI’AH DI DESA BULUH TELANG KECAMATAN PADANG TUALANG KABUPATEN LANGKAT - Lilis Syahroya; Sri Wahyuni (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Village development must be carried out in a planned manner and touch the real needs of the village community in the form of BUMDES, this is because the community is the one who knows more about the problems and potential of the village so that in this case the community is central to the village development process itself. The type of research is qualitative. Data collection methods include observation, interviews and documentation. The results of the research are that this BUMDes activity has clearly helped the people of Buluh Telang to further improve their welfare because seen from the programs implemented there is nothing that is detrimental to the community but instead increases or increases the community's income and the income of Buluh Telang village, the community can also enjoy it in the form of facilities. as well as infrastructure, from the BUMDes Buluh Telang activity program. Buluh Telang BUMDes is indeed in accordance with the Islamic economic outlook. This is because BUMDes in Batetangga Village are very relevant to the principles of Islamic economics, namely work, compensation, efficiency, professionalism and sufficiency. Apart from that, BUMDes activities also do not take too much interest and on average the community does not complain about interest on loan repayments so it can it is said that there is no element.